Business Plan : Squishy Dessert (Fluffy Donuts) / Muhamad Farhan Mohd Razali … [et al.] - Mohd Razali, Muhamad Farhan; Kamaruddin, Nur Aina Shafiqah; Abdul Hakim, Dzulqarnain; Norirwan, Nur Alissa Irwani; Wan Suden, Wan Muhamad Aliff Najmin; Mohd Harun, Nor Maisarah (2021)
This company is run as a partnership, with six individuals holding key positions in the company, including General Manager, Administration Manager, Marketing Manager, Operational Manager, and Financial Manager. The total business capital is RM 350,000, with each member contributing RM 50 000 and the remaining RM 50 000 coming from a Bank Islam’s loan. Fluffy Donnut is one of the top popular at our company. Squishy Dessert with motto “ Baked with Love” is located on No 45 Jalan Ah Sang, Kota Bharu Kelantan. Fluffy Donut’s is a company which is focus on dessert production especially donuts. Donuts is one of the most popular dessert in Malaysia. To make it more interesting our company has add a variation and innovation by implying our creativity and modern element suitable with modern life. Nowadays, colour is one of the important attraction to people and we have done a few R n D about it. So with our new innovation they can eat and taste variable of donuts and more tastier than before. We re expected this innovation our business will grow up and got a lot of demand from customer. This will give more profitable and our company can be more grower for long term.